A cross-sectional study of glucose regulation in young adults with very low birth weight: impact of male gender on hyperglycaemia. Issue 1 (3rd February 2012) - Sato, Ryosuke; Watanabe, Hiroshi; Shirai, Kenji; Ohki, Shigeru; Genma, Rieko; Morita, Hiroshi; Inoue, Eisuke; Takeuchi, Masahiro; Maekawa, Masato; Nakamura, Hirotoshi
Abstract : Objectives: To investigate glucose regulation in young adults with very low birth weight (VLBW; <1500 g) in an Asian population. Design: Cross-sectional observational study. Setting: A general hospital in Hamamatsu, Japan. Participants: 111 young adults (42 men and 69 women; aged 19–30 years) born with VLBW between 1980 and 1990. Participants underwent standard 75 g oral glucose tolerance test (OGTT). Primary and secondary outcome measures: The primary outcomes were glucose and insulin levels during OGTT and risk factors for a category of hyperglycaemia defined as follows: diabetes mellitus, impaired glucose tolerance (IGT), impaired fasting glycaemia (IFG) and non-diabetes/IGT/IFG with elevated 1 h glucose levels (>8.6 mmol/l). The secondary outcomes were the pancreatic β cell function (insulinogenic index and homeostasis model of assessment for beta cell (HOMA-β)) and insulin resistance (homeostasis model of assessment for insulin resistance (HOMA-IR)). Results: Of 111 young adults with VLBW, 21 subjects (19%) had hyperglycaemia: one had type 2 diabetes, six had IGT, one had IFG and 13 had non-diabetes/IGT/IFG with elevated 1 h glucose levels. In logistic regression analysis, male gender was an independent risk factor associated with hyperglycaemia (OR 3.34, 95% CI 1.08 to 10.3, p=0.036). Male subjects had significantly higher levels of glucose and lower levels of insulin during OGTT than female subjects (p<0.001 for glucose and p=0.005 for insulin by repeated measures analysis of variance). Pancreatic β cell function was lower in men (insulinogenic index: p=0.002; HOMA-β: p=0.001), although no gender difference was found in insulin resistance (HOMA-IR: p=0.477). In male subjects, logistic regression analysis showed that small for gestational age was an independent risk factor associated with hyperglycaemia (OR 33.3, 95% CI 1.67 to 662.6, p=0.022). Conclusions: 19% of individuals with VLBW already had hyperglycaemia in young adulthood, and male gender was a significant independent risk factor of hyperglycaemia. In male young adults with VLBW, small for gestational age was associated with hyperglycaemia.